Long-term effect of the combined use of powered toothbrush and triclosan dentifrice in periodontal maintenance patients - Anna Bogren (Blackwell Synergy, 2008)
Aim: To test the hypothesis of a superior clinical and microbiological effect of the combined use of powered toothbrush1triclosan-containing dentifrice compared with manual toothbrush1regular fluoride-containing dentifrice in periodontal maintenance patients. Material and Methods: A total of 128 periodontitis subjects involved in recall programmes were randomized to use either powered toothbrush with triclosandentifrice (test) or manual toothbrush and standard dentifrice (control). Supportive periodontal treatment was provided at baseline and every 6 months. Plaque, bleeding on probing (BoP), probing pocket depth (PPD) and relative attachment level (RAL) were scored at baseline, 1, 2 and 3 years. Subgingival plaque samples were taken and analysed for their content of 40 bacterial species at each examination interval. All analyses were performed by ‘‘intention-to-treat’’ protocol. Results: Both groups showed significant reduction in BoP, PPD and in mean total counts of the 40 bacterial species between baseline and 3 years, while plaque score and RAL remained almost unchanged. No significant differences between the two prevention programmes were found for any of the clinical outcome variables or in mean counts of the various bacterial species. Conclusions: The study failed to demonstrate superior clinical and microbiological effects of powered toothbrush1triclosan dentifrice compared with manual toothbrush1standard fluoride-dentifrice in periodontitis-susceptible patients on regular maintenance therapy.